2014
DOI: 10.1142/s0192415x14500694
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal Screening of Biologically Active Points for Upper Gastrointestinal Bleeding

Abstract: The purpose of this case-control study was to investigate the relationship between the electrical resistance of the skin at biologically active points (BAPs) on the main meridians and upper gastrointestinal bleeding (UGIB). Electrical resistance to direct current at 20 BAPs on the fingers and toes of 100 patients with (38 men, 12 women; mean age [range], 58.20 ± 19.62 [18-83] years) and without (27 men, 23 women; 49.54 ± 12.12 [22-74] years) UGIB was measured through electrodermal screening (EDS), based on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…According to previous research, higher electrical resistance of the meridian is often accompanied by organ function or suboptimal health conditions [ 13 ]. Research has also shown that lower electrical resistance often represents a better connection to the meridian [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to previous research, higher electrical resistance of the meridian is often accompanied by organ function or suboptimal health conditions [ 13 ]. Research has also shown that lower electrical resistance often represents a better connection to the meridian [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to previous research, higher electrical resistance of the meridian is often accompanied by organ function or suboptimal health conditions [ 13 ]. Research has also shown that lower electrical resistance often represents a better connection to the meridian [ 13 ]. Our results showed that the electrical resistance of the SCF-N group was lower than that of the control group, which could indicate that using the SCF-N needles for electro-acupuncture may achieve a better therapeutic effect than using untreated needles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different kinds of hypothesis on the nature of meridians [ 8 ]. They can be divided into four theoretical parts: those of nerve conduction theory [ 9 , 10 ], body fluid circulation theory [ 11 , 12 ], fascia and connective tissue structure doctrine [ 13 , 14 ], and biological field (or energy) doctrine [ 15 , 16 ]. Each hypothesis interprets the meridian essence of Chinese medicine from a different perspective, and these different hypotheses try to explore the essence of the meridian from individual reasonable points of view.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years studies have shown that electrodermal testing using both EAV and Chinese meridian system are accurate and reliable tool to measure electrodermal activities in APs. [10,12] There have also been pilot studies using either systems correlating electrodermal testing with pathophysiological conditions [11,[13][14][15] as well as evaluating therapeutic practices. [16,17] A 60-case retrospective study showed that specific changes in EAV testing from Lung and Lymphatic meridians were correlated to lung and upper respiratory symptoms, respectively.…”
Section: Introductionmentioning
confidence: 99%